The business case for sustainability in retrospect: A Scandinavian institutionalism perspective on the role of expert conferences in shaping the emerging "CSR and corporate sustainability space". Issue 3 (29th August 2018) - Breitbarth, Tim; Schaltegger, Stefan; Mahon, John
Abstract : This paper is concerned with the rise and, in retrospect, successful "positioning" of corporate social responsibility (CSR) and corporate sustainability as a management idea. It answers to calls that more research is required into the "business case for sustainability, " especially the link between rhetoric and reality. We allow for a narrative‐driven and dynamic perspective to frame the analysis of the discourse, rhetoric, and arguments in use during the emergence of "modern CSR" in Europe in the early 2000s. On the one hand, it shows that the European Union/Commission acted as an "enabler" of business case rhetoric. On the other hand, empirical evidence from two expert conferences series in Germany 2004–2008 leads to the conclusion that a wide coalition of interested parties continuously and progressively filled, shaped, and energized the early "CSR and corporate sustainability space" with presenting CSR as a rationale and progressive (management) idea.